Pengaruh Pemberian Reinforcement dan Motivasi Belajar terhadap Hasil Belajar Siswa Kelas VII Mata Pelajaran IPS SMPN 27 Surabaya: The Effect of Giving Reinforcement and Learning Motivation on Student Learning Outcomes for Class VII Social Studies Subjects at SMPN 27 Surabaya - Yusman, Salsabila Farodis (Jurnal Dialektika Pendidikan IPS, 2022)
This study was conducted as a result of the issue inadequate social studies learning outcomes, students' lack of attention during class, and some students' laziness when it came to completing tasks. The purpose of this study is ascertain how motivation and reinforcement affect students' learning outcomes in social studies classes at SMP Negeri 27 Surabaya. utilizing ex post facto quantitative studies of this kind. Ex post facto methodology was chosen since learning experiences occur within the learning process. In this study, 39 respondents from the entire class of class VII SMP Negeri 27 Surabaya were given questionnaires and learning outcomes to complete in order to gather data. Then, with the aid of SPSS 21.0, the data is controlled utilizing multiple regression analysis methods and partial correlation. The analysis's findings show that the first hypothesis, "Reinforcement," has an effect on the learning outcomes for social studies a tcount 2.891 and a sig value of 0.006, while the second hypothesis, "Motivation," also has an effect on the learning outcomes for social studies of 2.169 and a sig 0.037, and suggests giving reinforcement gifts and motivating students to learn. has an impact on the outcomes of social studies learning using ftable 7,280 and sig 0,002. According to the analysis's findings, reinforcement and learning motivation have favorable and sig impact on students' learning outcomes in social studies classes at SMP Negeri 27 Surabaya.